2015
DOI: 10.1177/1933719114532843
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Maternal Serum C-reactive Protein as a Predictor of Third-Trimester Impaired Glucose Tolerance

Abstract: Early identification of women at risk of IGT remains a priority, but the contribution of maternal BMI appears greater than hsCRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…There are publications that support this association in pregnancies that go on to be affected by GDM, although this may not remain significant once maternal obesity has been adjusted for [105]. In a series of 300 pregnancies with a 13% prevalence of GDM, Berggren et al (2014) log 10 highsensitivity C-reactive protein (hsCRP) was significantly increased, but became non-significant after adjustment for body mass index (BMI) [106]. A similar finding was reported in a second series, although a significant elevation in tumour necrosis factor alpha (TNFa) remains after accounting for BMI [107].…”
Section: Prediction and Prevention Of Gdmmentioning
confidence: 82%
“…There are publications that support this association in pregnancies that go on to be affected by GDM, although this may not remain significant once maternal obesity has been adjusted for [105]. In a series of 300 pregnancies with a 13% prevalence of GDM, Berggren et al (2014) log 10 highsensitivity C-reactive protein (hsCRP) was significantly increased, but became non-significant after adjustment for body mass index (BMI) [106]. A similar finding was reported in a second series, although a significant elevation in tumour necrosis factor alpha (TNFa) remains after accounting for BMI [107].…”
Section: Prediction and Prevention Of Gdmmentioning
confidence: 82%
“…However, some studies have contradicted the role of NLR in the prediction of GDM risk 21,23 . Berggren et al conducted a prospective nested case-control study 24 on women < 14 weeks pregnant. They showed that the hsCRP level of the pregnant women with abnormal glucose tolerance was higher than that of the pregnant women with normal blood glucose A vertical line was drawn from that value to the top points scale to determine the number of points that were assigned by that variable value.…”
Section: Discussionmentioning
confidence: 99%
“…Berggren and coworkers evaluated whether first-trimester hsCRP was predictive for third-trimester impaired glucose tolerance (IGT). hsCRP was positively associated with IGT, but, again, the association disappeared when adjusted for BMI ( 80 ). Thus far, the positive association of (hs)CRP and GD seems to be in part mediated by BMI.…”
Section: Other Inflammatory Mediatorsmentioning
confidence: 99%